2021
DOI: 10.3390/ijerph181910061
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Violence against Children and Its Increase during the COVID-19 Pandemic

Abstract: The aim of this study was to identify the epidemiological profiles of violence against children, victims, and their aggressors, and their correlations between socioeconomic and demographic factors analyzed before and during the COVID-19 pandemic. This was a cross-sectional, retrospective observational study based on a review of Individual Notification Forms from the Information System for Notifiable Diseases, including child victims of violence, under 18 years, assisted by a pediatric emergency service in Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
2
22
0
10
Order By: Relevance
“…Moreover, there were numerous temporary classroom closures, and closure of universities for several weeks during the 2020–2021 academic year. Finally, lockdown periods may have had negative impacts on the functioning of many families [ 20 ], including high rates of domestic violence toward juveniles [ 16 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were numerous temporary classroom closures, and closure of universities for several weeks during the 2020–2021 academic year. Finally, lockdown periods may have had negative impacts on the functioning of many families [ 20 ], including high rates of domestic violence toward juveniles [ 16 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these data precede the current COVID-19 pandemic, they are still relevant. Currently, these are the only available country-level data for Malawi that explain characteristics of violence and related factors among children; the COVID-19 pandemic has increased exposures to adverse childhood experiences such as orphanhood or loss of caregivers,32 social instability33 and direct violence exposures34 all of which have direct mental health issues for children. Existing vulnerabilities among families can have a more significant negative correlation among children through greater exposures to adverse childhood experiences.…”
Section: Discussionmentioning
confidence: 99%
“…To begin with, multiple reports raised attention to a significant increase in domestic violence during stay-at-home measures [87,88], which was attributable to familial distress and longer exposure of victims to perpetrators [89]. For children, studies found mixed results that varied according to geographical location [90][91][92][93][94]. However, results reporting decreases on notification rates were considered with worry [95], as underreporting could be a consequence of lack of contact with schools or of interruption of notification services [93,96,97].…”
Section: Recent Challengesmentioning
confidence: 99%